Analisis Wacana Kritis pada Novel Tempurung Karya Oka Rusmini dan Implikasinya dalam Pembelajaran - Hardinanto, Eko; Dwinata, Anggara (Ed-Humanistics : Jurnal Ilmu Pendidikan, 2022)
This research aims to find, describe, interpret, and explain the ideology of women against the domination of patriarchy, myths and customs in Oka Rusmini's Tempurung novel as teaching materials for senior high school students. The approach used in this research is descriptive qualitative. This study uses critical discourse analysis as a blade of analysis. The data source in this study is the Tempurung novel by Oka Rusmini, published by PT. Gramedia Widiasarana Indonesia in 2017. The steps taken in data collection are as follows: read over and over the whole novel to understand its contents completely, record important words, sentences, or data related to the problem under study, record and collect relevant theories related to research, conduct research based on existing theories, and draw conclusions. The steps in data processing are as follows: data description, data classification, data analysis, data interpretation, and evaluation. The data analysis techniques used were: processing and presenting data, reading the entire data, coding the data and descriptions, interpreting and explaining the data. The findings in this study are that the Tempurung novel is a reflection of the ideology of women's resistance to the patriarchal system, the ideology of fighting against myths created by patriarchy, and the ideology of resistance to tradition. The resistence is done to obtain equality in their rights and obligations, so that women can get freedom like men. The female characters in the Tempurung novel fight against the domination of patriarchy, myths, and their own cultural customs in order to realize equal rights between men and women. These findings can be used in the creating of text-based teaching materials as learning materials in the senior high school. The application of the concept of critical discourse analysis in learning will contribute to students’ critical thinking in solving various problems in life.